2022
DOI: 10.3390/microorganisms10101955
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Mycoplasma Haemoalbiventris’ and Tick-Borne Pathogens in Black-Eared Opossum (Didelphis aurita) from Southeastern Brazil

Abstract: The black-eared opossum (Didelphis aurita) is a South American synanthropic marsupial. The presence of opossums in domestic spaces is relevant in the One-Health context since they are hosts of pathogens and ectoparasites that may affect the health of domestic animals and humans. In this study, we aim to determine the occurrence of hemoplasmas and selected tick-borne pathogens in free-ranging black-eared opossums, along with their molecular characterization, hematological and biochemical evaluation and factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(69 reference statements)
1
4
0
Order By: Relevance
“…The anemia detected in all positive opossums is probably associated to other causes, such as inflammatory or chronic conditions, as all D. aurita of the present study presented such hematological finding. Platelet and plasma protein values ​​found in hemoplasma positive animals were within the reference value, corroborating with Orozco et al (2022) . The white blood cell count of these animals revealed leukocytosis, a finding closely related to inflammatory conditions or systemic stress mediated by cortisol ( Herrero-Cervera et al, 2022 ).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The anemia detected in all positive opossums is probably associated to other causes, such as inflammatory or chronic conditions, as all D. aurita of the present study presented such hematological finding. Platelet and plasma protein values ​​found in hemoplasma positive animals were within the reference value, corroborating with Orozco et al (2022) . The white blood cell count of these animals revealed leukocytosis, a finding closely related to inflammatory conditions or systemic stress mediated by cortisol ( Herrero-Cervera et al, 2022 ).…”
Section: Discussionsupporting
confidence: 80%
“…was found in 20% of the sampled black-eared opossums. Previous studies have found higher hemoplasma prevalence rates (ranging from 32.5-87.5%) in white-eared opossums from different geographic regions and biomes (Atlantic Forest and Cerrado) of Brazil ( Massini et al, 2019 ; Gonçalves et al, 2020 ; Orozco et al, 2022 ; Pontarolo et al, 2021 ). Differences in environment conditions may influence habits and behavior of the opossums, and threfore, their exposure to hemoplasmas, which may explain the low percentage of positive animals found herein.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations